2021
DOI: 10.1101/2021.01.12.426397
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Apolipoprotein M attenuates anthracycline cardiotoxicity and lysosomal injury

Abstract: Apolipoprotein M (ApoM) is an apolipoprotein that binds sphingosine-1-phosphate (S1P) and high-density lipoprotein. ApoM, via S1P signaling, is thought to protect cardiomyocytes from apoptosis, and ApoM plasma protein levels are inversely associated with increased mortality risk in human heart failure. Here, using a doxorubicin cardiotoxicity model, we identify ApoM as a novel regulator of myocardial autophagy. Doxorubicin treatment reduces ApoM plasma protein levels in wild-type mice and humans. Hepatic ApoM … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(116 reference statements)
0
1
0
Order By: Relevance
“… 23 A recent study revealed a cardioprotective role of ApoM‐bound S1P via myocardial autophagy. 68 Altogether, published and current findings of this study suggest that S1P signaling can protect the heart from pathological hypertrophy by different means.…”
Section: Discussionmentioning
confidence: 58%
“… 23 A recent study revealed a cardioprotective role of ApoM‐bound S1P via myocardial autophagy. 68 Altogether, published and current findings of this study suggest that S1P signaling can protect the heart from pathological hypertrophy by different means.…”
Section: Discussionmentioning
confidence: 58%